Repetitive exposure to a 7 Tesla static magnetic field of mice in utero does not cause alterations in basal emotional and cognitive behavior in adulthood - Hoyer, Carolin; Gass, Peter (Reproductive toxicology, 2012)
In the past three decades, magnetic resonance imaging (MRI) has been increasingly used in obstetrics to aid diagnostics of maternal and fetal conditions and has generally been considered a safe imaging method. However, the development of higher-performance systems employing, for example, stronger fields to improve the technique's diagnostic potential, necessitates on-going safety evaluation. Rodent studies provide an excellent opportunity to investigate not only acute but also long-term effects of magnetic field exposure in a systematic manner, and a behavioral analysis might help to uncover subtler effects which might result from magnetic field exposure of the vulnerable developing brain. We conducted a comprehensive investigation of emotional and cognitive behavior in adult mice which had been repeatedly exposed to a 7 Tesla static magnetic field in utero. Using well-validated tests, we did not observe any adverse behavioral alterations regarding emotional behavior as well as spatial and emotional learning.
Gesehen am 04.07.2018